2021
DOI: 10.1073/pnas.2023131118
|View full text |Cite
|
Sign up to set email alerts
|

Social distancing decreases an individual’s likelihood of contracting COVID-19

Abstract: Past research has established the value of social distancing as a means of deterring the spread of COVID-19 largely by examining aggregate level data. Locales in which efforts were undertaken to encourage distancing experienced reductions in their rate of transmission. However, these aggregate results tell us little about the effectiveness of social distancing at the level of the individual, which is the question addressed by the current research. Four months after participating in a study assessing their soci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 28 publications
(22 reference statements)
5
65
0
2
Order By: Relevance
“…In line with risk compensation theories (Hedlund, 2000;Yan et al, 2021), wearing face masks as a safety behavior lead to a reduction of physical distancing, a behavior that is associated with an increased risk for contracting Covid-19 (Chu et al, 2020;Fazio et al, 2021). Although both wearing an own face mask and observing other persons wearing face masks reduced distances, we found that face masks of other persons only resulted in a distance reduction when participants did not wear face masks by themselves.…”
Section: Discussionsupporting
confidence: 78%
“…In line with risk compensation theories (Hedlund, 2000;Yan et al, 2021), wearing face masks as a safety behavior lead to a reduction of physical distancing, a behavior that is associated with an increased risk for contracting Covid-19 (Chu et al, 2020;Fazio et al, 2021). Although both wearing an own face mask and observing other persons wearing face masks reduced distances, we found that face masks of other persons only resulted in a distance reduction when participants did not wear face masks by themselves.…”
Section: Discussionsupporting
confidence: 78%
“…Notably, other studies that employed elements of health behavior models for examining COVID-19 mitigation behaviors have reported effect estimates that are similar in magnitude to those we reported [ 14 , 15 ]. Furthermore, we leveraged a recent study [ 16 ], to demonstrate how the effect estimates we observed may be sufficient enough to contribute to variance in COVID-19 infection. This is critical to the contribution impact of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…This is critical to the contribution impact of our findings. Specifically, Fazio et al [ 16 ] showed that measures of social distancing predicted COVID-19 infection among U.S. adults; that more social distancing made it less likely to contract COVID-19 ( B = −0.202, p = .019). Based on their findings, we simulated the potential contributions of the effect estimates in our study to COVID-19 outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Deste modo, apesar dos possíveis impactos psicológicos, considera-se o distanciamento social como uma medida efetiva que diminui as chances de o indivíduo contrair a COVID-19 (Fazio et al, 2021), especialmente quando combinada ao isolamento de casos e à quarentena dos contatos (Aquino et al, 2020).…”
Section: Discussionunclassified